2002
DOI: 10.1093/toxsci/69.2.460
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cadmium on Bromosulfophthalein Kinetics in the Isolated Perfused Rat Liver System

Abstract: Bromosulfophthalein (BSP) is a relatively nontoxic organic anion used as an in vivo indicator of liver performance. Elimination of BSP via the biliary system following iv injection requires dissociation from albumin in plasma, translocation across the sinusoidal membrane, conjugation with glutathione within the hepatocyte, translocation across the bile canalicular membrane, and excretion in bile. The effects of cadmium (Cd), anin vivo hepatotoxicant in rats, on BSP kinetics in the isolated perfused rat liver (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…4, P Ͻ 0.05 vs. IgG ϩ LPS/Gal, n ϭ 5-7). Mice were injected with BSP to analyze the excretory function of the liver in vivo (23). We found that BSP excretion in control mice was 7.6 Ϯ 0.3 mg/ml and that LPS treatment decreased excretion of BSP down to 1.3 Ϯ 0.5 mg/ml, corresponding to an 83% reduction ( Fig.…”
Section: Resultsmentioning
confidence: 86%
“…4, P Ͻ 0.05 vs. IgG ϩ LPS/Gal, n ϭ 5-7). Mice were injected with BSP to analyze the excretory function of the liver in vivo (23). We found that BSP excretion in control mice was 7.6 Ϯ 0.3 mg/ml and that LPS treatment decreased excretion of BSP down to 1.3 Ϯ 0.5 mg/ml, corresponding to an 83% reduction ( Fig.…”
Section: Resultsmentioning
confidence: 86%
“…Thus, we hypothesize that chronic exposure to Cd in fish may disturb BA transport, triggering an accumulation of BAs in the hepatocytes. In support of this hypothesis, it has been shown that Cd causes a rapid decrease in bile flow and complete cholestasis in isolated perfused rat livers (Soto et al 2002). Moreover, cholestasis, by reducing bile flow, triggers malabsorption of dietary retinoids (de Vriese et al 2001;Weiss et al 2010).…”
Section: Retinol and Biliary Acid Metabolismmentioning
confidence: 92%
“…Hepatic clearance was considered another parameter of hepatic function 35, 36. Thirty minutes after the onset of the perfusion (t 30 ), 1 mg BSP (Sigma Co.) was added to the perfusate.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of BSP in bile samples (t 120 ) was measured at 580 nm with a ultraviolet‐visible spectrometer. Bile BSP excretion was expressed as a percentage of perfusate content (t 120 bile/t 30 perfusate · 100) 35, 36…”
Section: Methodsmentioning
confidence: 99%